Infância na publicidade: um estudo sobre o trabalho de crianças na publicidade na cidade de Natal-RN - Bezerra, Cássia de Castro (2008)
In Brazilian scene the child labor is a serious and relevant theme regarding issues that involve infancy, arousing the interest and concerning of public and private institutions, and organized civil society. Thus, the child labor is forbidden by the law, considered that the child worker have a distinguished life experience, especially because it is demanded them the early mature of some skill, generating implications on their physical, emotional, cognitive, social and psychological development. Observing those issues, we proposed think the child labor, over and above those considered the worst forms of one and more found in literature, what lead us to think the child labor in the advertising. In that way, this research aimed to investigate the insertion and development conditions of children who work in advertisements, and the possible effects on their lives in the face of that insertion. Participated of this study: three advertising agencies, six video producers companies, one child model s agent and five children with their respective families. Those children were four boys and two girls, with ages between seven and eleven years old, which one that have accomplished four or more advertisements, in Natal city, Rio Grande do Norte. Based on social-historical perspective, we used the semi-structured interview as methodological instrument, which underlays the comprehension of the data obtained in field research processes. This study revealed that when children are inserted in the advertising activities they are submitted to irregular and adverse work situations, what occurs in others productive activities mentioned in the literature. The data still exposed that the family is the main responsible to the children insertion in the advertisement work; moreover, there is an ambiguousness of wishes in relation of that activity. On the other hand, we realized that the legal content concerning to the child labor forbidding, carries contradictory aspects in face of the ECA s 149 article, that one, under some conditions, allows that a child take part in the activities of advertising context. This highlights the necessity of a rigorous evaluation of the children insertion in the advertising, in order to ensure the whole children and adolescents protection. This study put in evidence the complexity that involves the child labor in this context, mainly, due to the exposition and manipulation of the childish image on the media. Besides, we understand that the discussion on this subject should be stimulated and, therefore, enlarged this on over and above those considered the worst forms of child labor